Falsafah Adat Basandi Syarak Syarak Basandi Kitabullah dan Implikasinya dalam Bimbingan dan Konseling - Yuhaldi Yuhaldi (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2022)
The purpose of this research is to see how far guidance and counseling are able to help so that the meaning of philosophy is revived. The method used is the method of literature review. The results of this study are that guidance and counseling have a role in providing enlightenment to the community about the meaning of the Minangkabau customary philosophy. The conclusion of the research is that with guidance and counseling, people begin to see again the importance of religious values ​​and customs. This can be realized with the cooperation of all responsible elements starting from the village government, the clergy, traditional people, and academics and the community. Keywords: Adat, Kitabullah, Counseling